Forced Zika Virus Infection of Culex pipiens Leads to Limited Virus Accumulation in Mosquito Saliva - Sandra R. Abbo; Chantal B. F. Vogels; Tessa M. Visser; Corinne Geertsema; Monique M. van Oers; Constantianus J. M. Koenraadt; Gorben P. Pijlman (Viruses, 2020)
Zika virus (ZIKV) is a mosquito-borne pathogen that caused a large outbreak in the Americas in 2015 and 2016. The virus is currently present in tropical areas around the globe and can cause severe disease in humans, including Guillain-Barré syndrome and congenital microcephaly. The tropical yellow fever mosquito, Aedes aegypti, is the main vector in the urban transmission cycles of ZIKV. The discovery of ZIKV in wild-caught Culex mosquitoes and the ability of Culex quinquefasciatus mosquitoes to transmit ZIKV in the laboratory raised the question of whether the common house mosquito Culex pipiens, which is abundantly present in temperate regions in North America, Asia and Europe, could also be involved in ZIKV transmission. In this study, we investigated the vector competence of Cx. pipiens (biotypes molestus and pipiens) from the Netherlands for ZIKV, using Usutu virus as a control. After an infectious blood meal containing ZIKV, none of the tested mosquitoes accumulated ZIKV in the saliva, although 2% of the Cx. pipiens pipiens mosquitoes showed ZIKV–positive bodies. To test the barrier function of the mosquito midgut on virus transmission, ZIKV was forced into Cx. pipiens mosquitoes by intrathoracic injection, resulting in 74% (molestus) and 78% (pipiens) ZIKV–positive bodies. Strikingly, 14% (molestus) and 7% (pipiens) of the tested mosquitoes accumulated ZIKV in the saliva after injection. This is the first demonstration of ZIKV accumulation in the saliva of Cx. pipiens upon forced infection. Nevertheless, a strong midgut barrier restricted virus dissemination in the mosquito after oral exposure and we, therefore, consider Cx. pipiens as a highly inefficient vector for ZIKV.